IL-17A/CEBPβ/OPN/LYVE-1 axis inhibits anti-tumor immunity by promoting tumor-associated tissue-resident macrophages - Lei Zhao; Zonghan Wang; Yuying Tan; Jianan Ma; Wei Huang; Xiaoying Zhang; Chunhui Jin; Ting Zhang; Wentao Liu; Yong-Guang Yang (Cell Reports)
Summary: Tumor-associated macrophages (TAMs) are a critical component of the immunosuppressive tumor microenvironment, comprising monocyte-derived macrophages (MDM-TAMs) and tissue-resident macrophages (TRM-TAMs). Here, we discovered that TRM-TAMs mediate the pro-tumor effects of interleukin (IL)-17A and that IL-17A-driven tumor progression requires tumor cell production of osteopontin (OPN). Mechanistically, we identified CEBPβ as a transcription factor downstream of IL-17A in tumor cells and LYVE-1 as an OPN receptor on TRM-TAMs. IL-17A stimulates tumor cell production of OPN, and OPN/LYVE-1 signaling activates the JNK/c-Jun pathway, leading to the proliferation of immunosuppressive LYVE-1+ TRM-TAMs. Unlike its effect on LYVE-1+ TRM-TAMs, OPN interacts with α4β1 to promote the chemotaxis of LYVE-1− MDM-TAMs toward tumors. IL-17A neutralization, OPN inactivation in tumor cells, or LYVE-1 deletion in macrophages inhibited TAMs and enhanced anti-tumor immune responses and anti-PDL1 therapy. Thus, the IL-17A/CEBPβ/OPN/LYVE-1 axis offers a mechanism suppressing anti-tumor immune responses and, hence, an effective therapeutic target for cancer.